Conceptual framework for revitalisation of small-scale irrigation schemes in southern Africa - Mwendera, Emmanuel; Chilonda, Pius (Wiley, 2013)
This paper presents a conceptual framework for revitalising small-scale irrigation schemes which are either performing poorly or have partially collapsed due to a combination of infrastructural, social-economic, institutional and governance problems, among others. The framework is based on the understanding that an irrigation scheme consists of four mutually interlinked systems: the physical system, the cropping system, the economic system and the social-organisational system. The conceptual approach has two main elements: defining the methodology for revitalisation and implementation of the revitalisation process. The methodology is defined by conducting diagnostic studies to assess water availability, irrigation system, socio-organisation, economic, and market conditions of the scheme. The implementation process involves rehabilitating physical infrastructure, building the capacity of the farmers and extension workers to sustain the revitalised scheme and developing a framework for monitoring and evaluating the performance of that scheme. The whole revitalisation process is built on the foundations of learning from past experience (historical perspective) and continuous stakeholder consultation. The application of the framework and the hypothesis that improved understanding of existing schemes and improved training for farmers results in improved performance of small-scale irrigation schemes are yet to be investigated. The authors invite readers' reaction to the proposed framework.